MicroRNA and gene co-expression networks characterize biological and clinical behavior of rhabdomyosarcomas. (28th January 2017) - Missiaglia, Edoardo; Shepherd, Chris J.; Aladowicz, Ewa; Olmos, David; Selfe, Joanna; Pierron, Gaëlle; Delattre, Olivier; Walters, Zoe; Shipley, Janet
Abstract: Rhabdomyosarcomas (RMS) in children and adolescents are heterogeneous sarcomas broadly defined by skeletal muscle features and the presence/absence of PAX3/7-FOXO1 fusion genes. MicroRNAs are small non-coding RNAs that regulate gene expression in a cell context specific manner. Sequencing analyses of microRNAs in 64 RMS revealed expression patterns separating skeletal muscle, fusion gene positive and negative RMS. Integration with parallel gene expression data assigned biological functions to 12 co-expression networks/modules that reassuringly included myogenic roles strongly correlated with microRNAs known in myogenesis and RMS development. Modules also correlated with clinical outcome and fusion status. Regulation of microRNAs by the fusion protein was demonstrated after PAX3-FOXO1 reduction, exemplified by miR-9-5p. MiR-9-5p levels correlated with poor outcome, even within fusion gene positive RMS, and were higher in metastatic versus non-metastatic disease. MiR-9-5p reduction inhibited RMS cell migration. Our findings reveal microRNAs in a regulatory framework of biological and clinical significance in RMS. Highlights: RNAseq profiled miRNA expression in 64 rhabdomyosarcomas (RMS). MiRNA expression distinguished muscle and RMS on the basis of fusion gene status. Co-expression networks linked to function, clinical data and fusion gene status. Identified miRNAs, including miR-9-5p, altered by the PAX3-FOXO1 fusion protein. Demonstrated clinical and functional role for miR-9-5p in RMS.